QIYAS SEBAGAI SUMBER PENDIDIKAN AGAMA ISLAM - Puspa Dewi , Putri; Aprison , Wedra (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2023)
The sources of Islamic religious education that are generally widely known are the Al-Qur'an, Sunnah, Ijmak and Qiyas. Sources of Islamic religious education, some of which are agreed upon (muttafaq) by the ulama, and some which are still disputed (mukhtalaf). Qiyas is a source of law that has been unanimously agreed upon by all scholars and all schools of thought. Although in implementing them they may be different. These four are called mashadir as-syaria al-muttafaq 'alaih. Kuhujjahan Qiyas according to Ulama Jumhur ulama agree that qiyas is evidence whose source is the Al-Qur'an and Sunnah to determine the law of a new case whose law has not been determined by the text. Even the jumhur said that worship with the results of ijtihat from Qiyas is permissible and for new things it is mandatory to practice it.